1996
DOI: 10.1136/adc.75.3.175
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous growth in idiopathic short stature. European Study Group.

Abstract: Documenting the spontaneous growth pattern of children with idiopathic short stature (ISS) should be helpful in evaluating the effects of growth promoting treatments. Growth curves for children with ISS were constructed, based on 229 untreated children (145 boys and 84 girls) from nine European countries. The children were subdivided according to target range and onset of puberty, and the growth of these subgroups was evaluated from standard deviation scores (SDS). At birth, children with ISS were already shor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
38
1

Year Published

1998
1998
2010
2010

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(44 citation statements)
references
References 24 publications
5
38
1
Order By: Relevance
“…A similar pattern was seen for SH and LL SDS. This result confirms our and others' earlier findings (28,29). It also shows that HSDS for BA in young children severely over-predicts AH.…”
Section: Discussionsupporting
confidence: 82%
“…A similar pattern was seen for SH and LL SDS. This result confirms our and others' earlier findings (28,29). It also shows that HSDS for BA in young children severely over-predicts AH.…”
Section: Discussionsupporting
confidence: 82%
“…Even in ISS good responders to GH treatment seem to exist [9, 13], and the as yet poorly recognizable children with partial GHD may also have a good responsiveness. On the other hand, a large proportion of untreated ISS children seem to reach their genetic growth potential without GH treatment [9, 30]. We suggest that a tool should be developed for short children with maximum GH peaks >10 mU/l that identifies those who are most likely to benefit from GH treatment.…”
Section: Discussionmentioning
confidence: 99%
“…However, according to several papers reported height was as reliable as measured in the clinic [9, 23, 24]. It is also possible that some of our patients were measured at near-final rather than final height.…”
Section: Discussionmentioning
confidence: 62%
“…Crowne et al [21] suggested that the greater the bone age retardation, the less accurate the prediction methods. The RWT method analyses the greatest number of parameters potentially influencing the final height and most authors recognize it as the most accurate [11, 19, 24]. …”
Section: Discussionmentioning
confidence: 99%